Crystal structure of an apo form of Shigella flexneri ArsH protein with an NADPH-dependent FMN reductase activity - Vorontsov, Ivan I. (Cold Spring Harbor Laboratory Press, 2007)
The arsH gene or its homologs are a frequent part of the arsenic resistance system in bacteria and eukaryotes. Although a specific biological function of the gene product is unknown, the ArsH protein was annotated as a member of the NADPH-dependent FMN reductase family based on a conserved (T/S)XRXXSX(T/S) fingerprint motif common for FMN binding proteins. Presented here are the first crystal structure of an ArsH protein from Shigella flexneri refined at 1.7 Å resolution and results of enzymatic activity assays that revealed a strong NADPH-dependent FMN reductase and low azoreductase activities. The ArsH apo protein has an α/β/α−fold typical for FMN binding proteins. The asymmetric unit consists of four monomers, which form a tetramer. Buried surface analysis suggests that this tetramer is likely to be the relevant biological assembly. Dynamic light scattering experiments are consistent with this hypothesis and show that ArsH in solution at room temperature does exist predominantly in the tetrameric form.